Theoretical calculations of structural, electronic, and elastic properties of CdSe1−xTex: A first principles study. (9th June 2016) - Shakil, M; Zafar, Muhammad; Ahmed, Shabbir; Hashmi, Muhammad Raza-ur-rehman; Choudhary, M A; Iqbal, T
Abstract: The plane wave pseudo-potential method was used to investigate the structural, electronic, and elastic properties of CdSe1− x Te x in the zinc blende phase. It is observed that the electronic properties are improved considerably by using LDA+ U as compared to the LDA approach. The calculated lattice constants and bulk moduli are also comparable to the experimental results. The cohesive energies for pure CdSe and CdTe binary and their mixed alloys are calculated. The second-order elastic constants are also calculated by the Lagrangian theory of elasticity. The elastic properties show that the studied material has a ductile nature.